MSW student perceptions of sexual health as relevant to the profession: Do social work educational experiences matter?. (13th September 2016) - Winter, Virginia Ramseyer; O'Neill, Elizabeth; Begun, Stephanie; Kattari, Shanna K.; McKay, Kimberly
ABSTRACT: Many social work clients are at an increased risk for negative outcomes related to sexual behavior, including unwanted pregnancies and sexually transmitted infections (STIs). However, there is a dearth of literature on social work student experiences with these topics in social work classrooms and their perceptions about the topic's relevance to their practice. The purpose of this study is to explore relationships between experiences with STIs and contraception as topics in social work education and practica experiences on student perceptions toward sexual health as a relevant topic for social work. Among a national sample of MSW students ( N = 443), experiences with STIs and contraception as topics in practica was significantly related to perceptions toward sexual health's relevance to social work. Findings and implications are discussed.